2013
DOI: 10.1080/10739149.2013.832291
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Effective Tire Contact Area for Various Tread Patterns

Abstract: The effective tire-pavement contact area affects the relative damage of asphalt pavement and should be incorporated in both mechanistic and empirical response analyses of pavements. A new machine called ROTOCOM Wheel Tracker (RCWT) was designed and fabricated to capture the effective tire contact area apart from slab compacting, and conducting simulative laboratory wheel tracking tests. The main focus of this paper is laboratory measurement of effective tire contact areas for various tread patterns. Seven tire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…However, measurements and modeling data show that the vertical stress distribution at the tire-pavement interface is not uniform, and the contact area is not regularly circular [29] or rectangular [33,34]. Tire pattern and pavement texture influences are ignored in this assumption, so researchers have conducted extensive research on contact geometric characteristics [35,36]. Pillai et al [37] used the tire footprint to determine the tire-pavement contact area and obtained two simple predictive equations for tire-pavement contact area based on tire deflection and tire and wheel dimensional parameters found on the tire sidewall, as shown in Equations ( 1) and (2), with an error between the calculated and measured footprint areas within 15%.…”
Section: Geometric Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, measurements and modeling data show that the vertical stress distribution at the tire-pavement interface is not uniform, and the contact area is not regularly circular [29] or rectangular [33,34]. Tire pattern and pavement texture influences are ignored in this assumption, so researchers have conducted extensive research on contact geometric characteristics [35,36]. Pillai et al [37] used the tire footprint to determine the tire-pavement contact area and obtained two simple predictive equations for tire-pavement contact area based on tire deflection and tire and wheel dimensional parameters found on the tire sidewall, as shown in Equations ( 1) and (2), with an error between the calculated and measured footprint areas within 15%.…”
Section: Geometric Characteristicsmentioning
confidence: 99%
“…According to the 95% prediction band, the contact area of different tires also varies within a certain range. Muniandy et al [36] selected seven different tread-pattern tires for footprint image analysis, and their results showed that the tread pattern affected the tire-pavement contact area second only to tire load. Machemehl et al [53] used measured tire-pavement contact stress data to study the effect of tire pressure on pavements.…”
Section: Tirementioning
confidence: 99%
“…A tire-road contact patch can be obtained using the thermal paper method or paint footprint method [5]. The effective tire contact area should be further corrected for various tread patterns [6]. The contact patches of special tires, such as tractor tires, are more complex [7].…”
Section: Introductionmentioning
confidence: 99%
“…These factors include the design of tire tread pattern (groove type), inflation pressure, tire load and mechanical properties of material. Muniandy et al [3] found that an increment in inflation pressure by 50% will decrease the actual contact area by 17% while an increase of tire load by 50% will increase the actual contact area by 42%. Fwa et al [4] had identified that an increase in groove depth from 1mm to 9.8mm could reduce the hydroplaning rate by 9.8%.…”
Section: Introductionmentioning
confidence: 99%